TECHNOLOGY OF SCENARIO-STRATEGIC ANALYSIS AND PLANNING - Jumaniyazova Dilbar Azatovna; Morkhova Inessa Vyacheslavovna (Galaxy International Interdisciplinary Research Journal, 2024)
The entire range of educational services provided by state and non-state universities of various importance does not always adequately reflect the transformation of the requirements of the socio-economic sphere of modern society. The article discusses the importance of technology of scenario-strategic analysis and planning of organizations.